2014
DOI: 10.2138/am-2015-4850
|View full text |Cite
|
Sign up to set email alerts
|

Franciscan geologic history constrained by tectonic/olistostromal high-grade metamafic blocks in the iconic California Mesozoic-Cenozoic accretionary complex

Abstract: Subduction generated a NW-trending Andean arc along the Californian margin beginning at ~175 Ma. Coeval high-pressure (HP) transformation of oceanic crust in an east-dipping, subduction zone probably accompanied plate convergence, but recovered Franciscan eclogite and garnet blueschist blocks chiefly possess younger recrystallization ages of ~165-150 Ma. These Jurassic HP metamafic rocks were sequestered in a low-temperature environment well into Cretaceous time. Fragments of actinolitic rinds partially surrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 86 publications
(93 reference statements)
0
13
0
1
Order By: Relevance
“…In abstracts, Ross and Sharp () reported a garnet Sm‐Nd age of 190 ± 10 Ma from garnet amphibolite, and Page et al () reported a zircon U‐Pb age of 178 ± 7 from eclogite. Indirect evidence for early onset of Franciscan subduction is supplied by convergence along the western North American inferred on the basis of 180–170‐Ma arc magmatism and Early Jurassic terrane accretion in the Sierra Nevada and Klamath Mountains (Day & Bickford, ; Ernst, ; Fagan et al, ; Hacker, ; Wright & Fahan, ) and by Shervais et al () based on Middle Jurassic ages derived from the Coast Range Ophiolite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In abstracts, Ross and Sharp () reported a garnet Sm‐Nd age of 190 ± 10 Ma from garnet amphibolite, and Page et al () reported a zircon U‐Pb age of 178 ± 7 from eclogite. Indirect evidence for early onset of Franciscan subduction is supplied by convergence along the western North American inferred on the basis of 180–170‐Ma arc magmatism and Early Jurassic terrane accretion in the Sierra Nevada and Klamath Mountains (Day & Bickford, ; Ernst, ; Fagan et al, ; Hacker, ; Wright & Fahan, ) and by Shervais et al () based on Middle Jurassic ages derived from the Coast Range Ophiolite.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Anczkiewicz et al () argued that garnet‐amphibolite formed during the earliest stages of subduction and interpreted a Lu‐Hf garnet age from a single amphibolite sample to date subduction initiation circa 169 Ma. More recently, Ernst () inferred that convergence began at 175 Ma based on the timing of early arc magmatism and terrane accretion in the Sierra Nevada and Klamath Mountains.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, thinner, especially mud-richer sections may convert to shale-matrix, fault-zone mélange, some of which may form and accrete incrementally (e.g., Rowe et al, 2013). The Subduction Channel model (Cloos, 1982(Cloos, , 1984Shreve, 1988a, 1988b) is used widely to explain formation and emplacement of laterally extensive and generally thick shale-matrix or serpentinite-matrix mélange units within accretionary complexes (e.g., Hansen, 1992;Vannucchi et al, 2008;Blanco-Quintero et al, 2011;Ukar, 2012;Ogawa et al, 2014;Ernst, 2015). In the Subduction Channel model, continuous ductile flow and pervasive deformation of the shale or serpentinite matrix are essential for offscraping, fragmentation, and mixing of high-and low-grade blocks and other rocks within mélange packages (Cloos, 1982;Cloos and Shreve, 1988a;Ukar, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The Franciscan Complex of western California was recognized during the development of plate tectonic theory as a subduction accretionary complex. For many it became the archetypical accretionary complex (e.g., Ernst, 1970Ernst, , 2015Wakabayashi, 2015). The Complex was initially divided into three (possibly fault-bounded) geographic belts-the Eastern, Central, and Western belts-with each belt characterized by particular rock types, rock ages, and a low-temperature metamorphic facies (blueschist, prehnite-pumpellyite, and zeolite facies-from east to west; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…La présence de phengite et de zircon permien cristallisé sous conditions métamorphiques du faciès à éclogite au sein de la roche hôte quartzofeldspathique indiquent que l'éclogite a été métamorphisée en place, avec le schiste comme unité cohérente du terrane de croûte d'arc continental de Yukon-Tanana, plutôt qu'un mélange associé à une subduction de croûte océanique du terrane de Slide Mountain. Des similarités pétrologiques, géochimiques, géochrono-logiques et structurales lient les éclogites de St-Cyr à d'autres lieux de hautes pressions au Yukon, ce qui indique que les INTRODUCTION High-pressure metamorphic assemblages formed in Pacifictype convergent margins, such as the iconic Franciscan complex (Ernst 2015), are found along the western North American margin from Alaska to Mexico . The Yukon-Tanana terrane in the Canadian Cordillera preserves both Mississippian and Permian high-pressure rocks.…”
Section: Résuméunclassified